Antityrosinase Inhibitory Activity of Phytochemicals from Alpinia aquatica Roscoe - Nissha Bharrathi Romes; Wan Mohd Nuzul Hakimi Wan Salleh; Hasnah Mohd Sirat; Zaini Assim (Tabriz University of Medical Sciences, 2020)
Background: Genus Alpinia are commonly used as spices and ingredients in traditional medicines. In the present study, we attempted to isolate the phytochemicals from Alpinia aquatica and evaluate their tyrosinase inhibitory activity.Methods: Phytochemical constituents of the extract were investigated using various chromatographic and spectroscopic methods. The chemical structures of the isolated phytochemicals were established by analysis of their spectroscopic data, as compared to that of reported data. Tyrosinase inhibitory activity was also tested on the extracts and selected compounds using mushroom tyrosinase as the enzyme.Results: Fractionation and purification of the extracts of Alpinia aquatica afforded seven known compounds which are 5-hydroxy-3,7,4'-trimethoxyflavone (1), 4',5-dihydroxy-3,7-dimethoxyflavone (2), 2-methoxy-8-(2',4',5'-trimethoxyphenyl)-1,4-naphthaquinone (3), cis-3S-(2',4',5'-trimethoxyphenyl)-4S-[(E)-2''',4''',5'''-trimethoxystyryl]cyclohexene (4), 2,4,5-trimethoxybenzaldehyde (5), stigmasterol (6) and β-sitosterol (7). The ethyl acetate extract of pseudostems possessed the highest tyrosinase inhibition of 31.0% among the extracts, while compound (1) gave tyrosinase inhibition of 48.0%.Conclusion: Compounds (3) and (4) were isolated for the first time from A. aquatica and Alpinia genus. These phytochemical results suggest that the extracts could assist as a potential source of bioactive compounds. Further research is needed in which the extract could possibly be exploited for pharmaceutical use.